(untitled) (Perner’s Contacts, 2022)
The aim of the current research is to determine the effect of initial imperfections on the loss of stability of a laterally loaded cylindrical shell. This paper describes the ongoing second phase of experimental verification, which currently consists of the verification of newly produced experimental specimens. For this reason, this paper focuses only on a variant of the model without intentionally creating initial imperfections. The results of geometrically and materially nonlinear numerical analysis (GMNA) are compared with the loading outcomes of two experimental models in a universal testing machine. The measure of conformity is then the value of the ultimate load at which the stability of the transversely loaded cylindrical shell under consideration is lost. Furthermore, the progress and conformity of the individual load curves are also assessed. If a sufficiently close agreement between the results of the numerical analyses and the outputs of the new experimental specimens is confirmed, then the next step of the second phase of experimental verification is enabled, which consists in carrying out experiments on specimens with a deliberately created geometric initial imperfection.